Implementation Model of Regional Spatial Planning Policy in Realizing Sustainable City Development in Banjar City: (Banjar City Regional Regulation Study No. 9 of 2014 concerning Banjar City Spatial Planning) - David Abdillah Al Amin; Kamal Alamsyah; Ummu Salamah (Pasundan Social Science Development, 2022)
The main problems in this study are directed at the model of the implementation of the Regional Spatial Planning policy in practice has not run effectively in realizing sustainable urban development in Banjar City. The research method used by researchers is descriptive analysis, while the type of approach used in this study is qualitative. Descriptive analysis method aims to describe complex social reality by applying concepts that have been developed in social science / public administration. Whereas the qualitative approach was chosen with the consideration that this approach is expected to obtain true data and be able to examine research problems in depth so that the expected results can be obtained. The results of the study can be stated that there are factors that lead to the implementation of the Regional Spatial Plan (RTRW) policy in realizing sustainable city development in Banjar City can run effectively, namely Policy standards and objectives, Resources and incentives, The quality of inter-organizational relationship , The characteristics of implementation agencies, the economic, social and political environment and the 'dispositon' or response of the implementers. However, based on the results of the research, these factors have not been entirely effective. The factors that have not been implemented effectively are the Policy standards and objectives and the "dispositon" or response of the implementers. Therefore there are still problems faced with regard to the Regional Spatial Planning (RTRW) policy, so that it has not been able to provide the best way to regulate, make the best use of spatial planning in the region by considering the level of needs, especially the development sector in urban areas. Disamaping also the results of the study suggest that there is a model in implementing the Regional Spatial Plan policy in realizing sustainable city development in Banjar City, namely synthesis / hybrid models by elaborating the interests of the Central Government, Provincial and Community Participation. This means that the RTRW policy both in planning and in its implementation elaborates by involving the Central Government, West Java Province and the participation of the Banjar City community. Although the policy is decentralized, the central and provincial governments still have a stake in controlling and overseeing the policies of the regional layout plan in realizing sustainable urban development in Banjar City.